MAGNETOLELLURIC DATA COLLECTION AND ANALYSIS IN THE SES SENSITIVE SITE OF IOANNINA AREA (GREECE) - Rokityansky I.I.; Varotsos P.A. (My University, 2006)
Two independent magnetotelluric sounding (MTS) studies in Ioannina (NW Greece) area have been reported. Their conclusions, however, differ essentially. To proceed in the correct understanding of the geoelectrical structure in that area, additional detailed observations in several sites were made. The analysis of the new data proves that the conclusion of Pham et al. [Pham, V.N., Boyer, D., Le Mouel, J.L., Chouliaras, G., Stavrakakis, G.N., 1999. Electromagnetic signals generated in the solid Earth by digital transmission of radio-waves as a plausible source for some so-called "seismic electric signals". Phys. Earth Planet. Interiors, 114, 141-163] claiming a globally high resistivity structure in the area does not hold. Moreover the present analysis strengthens the model that the main geoelectrical structure of Ioannina area (being considered along a regional profile of the NE-SW direction) is characterized by a high resistive formation in the upper crust, but inside it a set of narrow conductors (elongated in the NW-SE direction) exists. These conductors provide support for the possibility that seismic electric signals emitted from distances of the order of 100 km can be recorded at the Ioannina SES sensitive site. © 2006 Elsevier Ltd. All rights reserved.
Keywords: CONDUCTIVITY STRUCTURE; MAGNETOTELLURIC SOUNDING; PRINCIPAL DIRECTIONS; SEISMIC ELECTRIC SIGNAL